Pengaruh Kompetensi, Independensi, Fee Audit Dan Audit Tenure Terhadap Kualitas Audit: (Studi Kasus Pada Kantor Akuntan Publik Sukardi Hasan & Rekan di Tangerang) - Adam Desvian Muhidin; Desy Arigawati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The purpose of this study was to analyse the effect of competence, independence, audit fees and audit tenure on audit quality. This research method is quantitative research by testing between variables. The population in this study were all independent auditors who worked at the Public Accounting Firm (KAP) in Tangerang. The sample used in this study was 44 auditors. The sample determination method used in this study is Simple Random Sampling, the data collection method uses a survey method with a questionnaire. The data analysis method in this study used SPSS version 29.0. The result of this study is that the competency variable has a positive and significant effect on audit quality. This shows that the more competence an auditor has, the better the audit quality will be. The independence variable has a positive and significant effect on audit quality. This shows that the better the independence of an auditor, the better the audit quality will be. The audit fee variable has no significant effect on audit quality. The audit tenure variable has a positive and significant effect on audit quality. The variables of competence, independence, audit fees and audit tenure together have a significant effect on the resulting audit quality.